Analysis of the Tax System, Fairness and the Possibility of Fraud Detection on Perceptions of Tax Evasion - Adi Sucipto (Yayasan Adra Karima Hubbi, 2024)
Fraud behavior in taxation is a problem that often occurs, one of the acts of fraud committed is tax evasion. The impact of tax evasion itself raises many perceptions, especially individual taxpayers who are in KPP Pratama Soreang. The purpose of this study was to determine the effect of the taxation system, justice and the possibility of detecting fraud on perceptions of taxpayers about tax evasion. This research uses descriptive verification method with quantitative approach. Source of data used are primary data resulting from the distribution of questionnaires to taxpayers of 100 respondents. Based on the results of the study showed that partially the taxation and justice system did not significantly influence the perception of tax evasion. However, the possibility of partial fraud being detected has a significant negative effect on perceptions of tax evasion with indicators of tax rates imposed in Indonesia and stringent checks. From the results of the study it is expected that tax officials can improve the quality of audits because it can reduce tax evasion in KPP Pratama Soreang.